2017
DOI: 10.3892/mmr.2017.7809
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus p7 induces mitochondrial depolarization of isolated liver mitochondria

Abstract: Hepatitis C virus (HCV)‑encoded protein p7 is a viroporin that acts as an ion channel and is indispensable for HCV particle production. Although the main target of HCV p7 is the endoplasmic reticulum, it also targets mitochondria. HCV‑infected cells show mitochondrial depolarization and ATP depletion; however, the function of HCV p7 in mitochondria is not fully understood. The present study demonstrated that treatment of isolated mouse liver mitochondria with the synthesized HCV p7 protein induced mitochondria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Furthermore, Ma et al demonstrated that the IVA M2 viroporin exhibits proton channel activity and induces ROS production required to antagonize autophagy and amplify the MAVS signaling pathway [ 91 ]. Lee et al, 2020, described that HCV has two viroporins: P7, which permeabilizes the mitochondrial membrane via interaction with phosphatidyl serine (a negatively charged phospholipid) located in the lipid rafts of membranes, and another HCV core viroporin, which is located in the outer mitochondrial membrane and decreases with an increase in ROS production [ 71 , 92 ].…”
Section: Mitochondrial Ros and Viroporinsmentioning
confidence: 99%
“…Furthermore, Ma et al demonstrated that the IVA M2 viroporin exhibits proton channel activity and induces ROS production required to antagonize autophagy and amplify the MAVS signaling pathway [ 91 ]. Lee et al, 2020, described that HCV has two viroporins: P7, which permeabilizes the mitochondrial membrane via interaction with phosphatidyl serine (a negatively charged phospholipid) located in the lipid rafts of membranes, and another HCV core viroporin, which is located in the outer mitochondrial membrane and decreases with an increase in ROS production [ 71 , 92 ].…”
Section: Mitochondrial Ros and Viroporinsmentioning
confidence: 99%
“…Delayed cleavage of E2-p7 is important for mature viral particle assembly [162]. HCV p7 also causes depolarisation of the mitochondrial membrane and mitochondrial acidification which promotes HCV particle production [163]. The key features of the p7 structure are conserved among HCV genotypes.…”
Section: P7 Structure and Functionmentioning
confidence: 99%
“…As expected, Gd 3+ ions significantly blocked the macroscopic currents triggered by p7 ( Figure 5A). Because p7 has been known to target the ER, mitochondria, and plasma membrane, and can cause mitochondrial depolarization in cells [12] and in purified mitochondria [19], we isolated mitochondria from mouse liver and applied Gd 3+ ions for 10 min, followed by staining with the ∆ψm indicator (JC-1) to examine the inhibitory effect on mitochondrial depolarization. We found that p7 induced mitochondrial depolarization, but Gd 3+ ions had no significant effect on the membrane potential of intact mitochondria.…”
Section: Gd 3+ Ions Block the Channel Activity Of P7 In The Bilayer Amentioning
confidence: 99%